Synthesis and characterization of metal-organic framework (MOF) CoBTC as a non-enzymatic electrochemical biosensor for glucose. Issue 1 (February 2021) - Abrori, S A; Trisno, M L A; Aritonang, R A; Anshori, I; Nugraha,; Suyatman,; Yuliarto, B
Abstract: Diabetes mellitus is one of the highest causes of death globally, caused by high glucose levels in the blood. Thus, monitoring glucose levels in the blood becomes very important. Non-enzymatic glucose detection is currently an emerging research area, one of which uses Metal-Organic Material (MOF), which has advantages such as having a large surface area and having many micropores. The purpose of this study was to synthesize MOF CoBTC and see its performance as a glucose sensor. The synthesis method used is the solvothermal method, while the sensor performance testing method uses an electrochemical method. The solvothermal method of the CoBTC was carried out at a temperature of 100°C, and the duration of synthesis of 10 hours. The structural characterization of the synthesized samples by X-Ray Diffraction (XRD), Scanning Electron Microscopy (SEM), Fourier Transform Infrared (FTIR) Spectroscopy, Brunauer Emmett Teller (BET) Surface Area Analyzer showed that we successfully synthesized CoBTC. Furthermore, the electrochemical characterization via cyclic voltammetry (CV) and amperometry results showed the sensor's optimal working potential at 0.4 V, the sensitivity of 53.455 μA mM-1 cm-2 and the limit of detection (LOD) at 5.49 μM.